Employee Well-being and Turnover Intention Among New Graduate Nurses in Hospitals of Dali, the People’s Republic of China - Cuixian, Li; Wichaikhum, Orn-Anong; Abhicharttibutra, Kulwadee (Nursing Journal CMU, 2023)
Employee well-being is an important factor in turnover intention among new graduate nurses. This descriptive correlational study aimed to describe employee well-being, determine the level of turnover intention, and examine the relationship between employee well-being and turnover intention of new graduate nurses in hospitals in Dali, the People’s Republic of China. The sample consisted of 260 new graduate nurses working in three Dali hospitals. The research instruments were the Chinese version of the Employee Well-being Scale (EWBS) and the Turnover Intention Questionnaire (TIQ). The Cronbach’s alpha of the EWBS and TIQ were 0.94 and 0.89, respectively. Descriptive statistics and Spearman’s rank-order correlation were used for data analysis. Results revealed that the overall mean score of employee well-being of new graduate nurses was 3.97 (SD = .72). Turnover intention of new graduate nurses was at a moderate level ( = 3.77, SD = .96). There was a significant negative relationship between employee well-being and turnover intention (r = -.341, p < .01). The findings of this study could provide baseline data for nurse administrators to design strategies to improve employee well-being and minimize the turnover intention of new graduate nurses.